Pesquisa descritiva da inovação tecnológica para simulação em Realidade Virtual e Aumentada sob a perspectiva da indústria 4.0 e os sistemas virtuais de produção - Ribeiro Neto, Albino (2014)
The present work attempts to the possibility of using Virtual Reality and Augmented Reality tools in conjunction with Advanced Manufacturing (Industry 4.0). In order to better understanding it is demonstrated through examples the use of virtual tools to visualize and interact with Digital Twins of industrial equipment and other technologies of Virtual Production Systems. The goal is to present an overview of the innovation in Virtual and Augmented Reality technologies and their use on the factory floor. The chosen methodologies to base the thesis on were the descriptive research, case studies and semi-structured interviews, to better describe the current context and expectations of improvements in the management of activities inside a factory floor. Various approaches will be presented on the Internet of Things, Industrial Internet of Things and Industry 4.0, which is also known as advanced manufacturing in Brazil. The contribution of this work is in establishing the main service fields where the Virtual and Augmented Reality technologies can be applied and their lines of research/operation for the Industry 4.0. As a result, it is expected to provide an increase in productivity and consequently in the competitiveness of the industry in general.